Pengaruh Kecanggihan Teknologi, Kemampuan Teknik Personal, Dan Pengalaman Kerja Terhadap Efektivitas Sistem Informasi Akuntansi Di Lembaga Perkreditan Desa (Lpd) Se- Kecamatan Denpasar Selatan - Ni Luh Titaria Juliartini; Ni Wayan Alit Erlina Wati; Ni Putu Trisna Windika Pratiwi (Hita Akuntansi dan Keuangan, 2023)
The goal of this study is to find out "how technological maturity, individual technical skills, and professional experience affect the efficiency of LPD's accounting information system in the South Denpasar district." This study was done in the LPD South District of Denpasar. The sample size for this study was 33 people, and purposive sampling was used to choose them. The questionnaire method is used to get the information. Multiple linear regression analysis was the method that was used to look at the data.Based on the results of the study, in which 33 people filled out questionnaires, we can say that technological maturity, personal technical skills, and work experience all make accounting information systems work better. It is known that if you want to make the accounting information system work better, you need to pay attention to the things that affect it.